Evolving Treatment Paradigms in Non-clear Cell Kidney Cancer - Vaishampayan, Ulka (Curr Treat Options Oncol, 2018)
With no therapy specifically approved for non-clear cell cancers of the kidney, this disease remains an orphan site. Clear cell renal cancers (ccRCC) have seen a flurry of activity with multiple agents gaining Food and Drug Administration (FDA) approval in recent years. Simultaneously, non-clear cell RCC (ncRCC) have also seen a fair share of activity and exploration of new agents in development but no specific FDA approvals. Non-clear cell RCC is a mixed bag of multiple types of tumors originating in the kidney with distinct clinical molecular and genetic characteristics that vary significantly from clear cell carcinoma of the kidney. Conventionally, non-clear cell RCC have been treated with the same therapies as clear cell RCC. The clinical trials are typically conducted in ccRCC and the FDA approval covers non-clear cell cancer as well. Few randomized clinical trials have been conducted specifically for ncRCC. With the advent of molecular and tumor genomic testing, leading to discovery of targets and associated therapies for ncRCC, a specific review of the state of management of this disease is timely and clinically relevant.